Rationale and protocol for the efficacy, safety and tolerability of nangibotide in patients with septic shock (ASTONISH) phase IIb randomised controlled trial. Issue 7 (7th July 2021) - Francois, Bruno; Lambden, Simon; Gibot, Sebastien; Derive, Marc; Olivier, Aurelie; Cuvier, Valerie; Witte, Stephan; Grouin, Jean-Marie; Garaud, Jean Jacques; Salcedo-Magguilli, Margarita; Levy, Mitchell; Laterre, Pierre-François
Abstract : Introduction: Septic shock is the subgroup of patients with sepsis, which presents as vasopressor dependence, an elevated blood lactate concentration and is associated with a mortality of at least 30%. Expression of the triggering receptor expressed on myeloid cells 1 (TREM-1) pathway, measured using a serum biomarker of pathway activation (soluble TREM-1, sTREM-1) has been associated with outcome in septic shock. Preclinical and early phase patient data suggest that therapeutic modulation of this pathway may improve survival. Methods and analysis: Efficacy, Safety and Tolerability of Nangibotide in Patients with Septic Shock is a phase IIb randomised controlled trial that will take place in up to 50 centres in seven countries and recruit 450 patients with septic shock to receive either placebo or one of two doses of nangibotide, a novel regulator of the TREM-1 pathway. The primary outcome will be the impact of nangibotide therapy on the change in Sequential Organ Failure Assessment score from a baseline determined before initiation of study drug therapy. This will be assessed first in the patients with an elevated sTREM-1 level and then in the study population as a whole. In addition to safety, secondary outcomes of the study will include efficacy of nangibotide in relation to sTREM-1 levels in terms of organ function, mortality and long-term morbidity. This study will also facilitate the development of a novel platform for the measurement of sTREM-1 at the point of care. Ethics and dissemination: The study has been approved by the responsible ethics committees/institutional review boards in all study countries: Belgium: Universitair Ziekenhuis Antwerpen, France: CPP Ile de France II, Denmark: Region Hovedstaden, Spain: ethics committee from Valld'Hebron Hospital, Barcelona, Finland: Tukija, Ireland: St. James' Hospital (SJH) / Tallaght University Hospital (TUH) Joint Research Ethics Committee, USA: Lifespan, Providence Trial registration numbers: EudraCT Number: 2018-004827-36 and NCT04055909 .